Chemotherapy for gynecological malignancies in organ transplantation patients: report of two cases. Issue 6 (1st October 2008) - Tao, X.; Kavanagh, J. J.
Abstract : Long-term risk of gynecological malignancies in organ transplantation patients has increased compared with that of the general population owing to the use of immunosuppressive agents. Treatment, especially chemotherapy, in these patients should take into consideration their renal function and the effects of immunosuppressive agents. We here present two case reports of patients with chemotherapy-treated gynecological malignancies who had previously received organ transplantation. The first case, a rare occurrence of simultaneous carcinomas of the uterine corpus and ovary, is the first such report in the English literature describing chemotherapy for concurrent serous papillary ovarian carcinoma and endometrioid endometrial carcinoma in a renal transplant patient. The second case report, describing chemotherapy for cervical cancer following two organ transplantation, also rare, is the first such report in the English literature and the first report of cervical cancer after heart–kidney transplantation.